(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The writer Kakimzhan Kazybayev occupies a prominent place in the history of literature due to his originality. The value of his works of art is that the writer describes without distorting the reality that corresponds to a particular historical period. The author expresses views on the language, the plot, the system of the novel’s images, and makes a comparative analysis. In order to demonstrate the skill, artistic intent of the writer examples from the novel are cited. The author concludes that in his prose works the writer does not tend to exaggerate the «white spots» of the history, and seeks to tell the truth about the described time and historical events of the time in their relationship that constitute the artistic skills of the writer.